Detailing a case of cyber fraud through telephone in Brazil: From the choice of elderly victims, spoofing until social engineering manipulation - Morgado, Eduardo M. [UNESP]; Albino, João Pedro [UNESP]; de Lima, Ana Cláudia Pires Ferreira [UNESP]; Távora, Carla Gonçalves [UNESP]; Bucchianico, Ivany (IGI Global, 2023)
The goal is to initiate a discussion over the measures to protect the victims, whom unfortunately, in Brazil, composes 30% of elderly people (older than 60 years old). The case report portrays the scam through spoofing, programs that change the caller's identification in a communication, together with Social Engineering, to trick the victim into carrying out operations in the bank's application, thus encouraging transfers to the scammer's account. The victim ended up following these guidelines and made appointments to send money to the scammer, however, he ended up suspecting the situation, decided to interrupt that communication and seek the bank branch for clarification, thus managing to cancel the appointments and reverse the transfer amounts. Actions need to be taken, urgently, because the predictions show a gigantic increase of this type of fraud.